Progress in Pattern Recognition, Image Analysis and Applications - Rueda, Luis (Springer, 2017)
This book constitutes the refereed proceedings of the 12th Iberoamerican Congress on Pattern Recognition, CIARP 2007, held in Valparaiso, Chile, November 13-16, 2007. The 97 revised full papers presented together with four keynote articles were carefully reviewed and selected from 200 submissions. The papers cover ongoing research and mathematical methods for pattern recognition, image analysis, and applications in areas such as computer vision, robotics, industry and health.